2019
DOI: 10.1002/jimd.12175
|View full text |Cite
|
Sign up to set email alerts
|

Glucose transporter type 1 deficiency syndrome and the ketogenic diet

Abstract: Glucose transporter type 1 deficiency syndrome (GLUT1DS) is characterised by deficient glucose transport over the blood‐brain barrier and reduced glucose availability in the brain. This causes epilepsy, movement disorders, and cognitive impairment. Treatment with ketogenic diet provides ketones as alternative energy source. However, not all GLUT1DS patients are on dietary treatment (worldwide registry: 77/181 [43%] of patients). The current 25‐year experience allows evaluation of effects and tolerability of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 12 publications
1
37
0
4
Order By: Relevance
“…The age at the onset of symptoms was lower in our patients with epilepsy and in the SLC2A1 (+)-group, and the time from debut to the onset of treatment was significantly higher. Most studies describe a delay of at least 4 years from debut to the onset of the diet [ 13 , 17 , 19 ]. Therefore, KDT should be onset when a GLUT1DS is suspected, although the definitive diagnosis is not made.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The age at the onset of symptoms was lower in our patients with epilepsy and in the SLC2A1 (+)-group, and the time from debut to the onset of treatment was significantly higher. Most studies describe a delay of at least 4 years from debut to the onset of the diet [ 13 , 17 , 19 ]. Therefore, KDT should be onset when a GLUT1DS is suspected, although the definitive diagnosis is not made.…”
Section: Discussionmentioning
confidence: 99%
“…The current standard treatment for GLUT1DS are the KDT, especially the CKD [ 4 , 6 , 12 , 19 , 20 ]. Recent reviews have reported that 60% of the patients were seizure-free after the implementation of the diet, and 80% of patients with movement disorders improved [ 3 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with GLUT1-DS have historically been treated with the KD since it provides an alternate source of energy (ie, ketone bodies) that circumvents the brain's glucose deficiency ( Figure 1) and alleviates most of GLUT1 deficiency symptoms. 70,71 KD metabolites, principally circulating ketone bodies such as acetoacetate and beta-hydroxybutyrate, act as substitutes for glucose by subsequent conversion into acetyl-CoA, which then enters the citric acid cycle and is terminally oxidized in mitochondria to produce ATP. Ketone bodies are mostly generated by the liver, enter the peripheral circulation, and are then transported into the brain through (MCTs); they do not require a functional glucose transporter to be utilized.…”
Section: Kd Contraindicationsmentioning
confidence: 99%
“…Available efficacy data confirm that KDTs can be maintained with good compliance in pediatric and adolescent patients [ 1 , 8 ]. In particular, in a recent review by Schwantje and colleagues [ 9 ], it has been demonstrated that compliance with a ketogenic diet (KD) is higher than 80% in the GLUT1DS population. The conditions turn out to be more complicated for DRE patients.…”
Section: Introductionmentioning
confidence: 99%